2020
DOI: 10.1016/j.mayocp.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection and COVID-19 During Pregnancy: A Multidisciplinary Review

Abstract: The global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of coronavirus disease 2019 (COVID-19), has been associated with worse outcomes in several patient populations, including the elderly and those with chronic comorbidities. Data from previous pandemics and seasonal influenza suggest that pregnant women may be at increased risk for infectionassociated morbidity and mortality. Physiologic changes in normal pregnancy and metabolic and vascular changes in high-risk pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
224
2
35

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(266 citation statements)
references
References 86 publications
5
224
2
35
Order By: Relevance
“…Clinical manifestations appeared in SARS-CoV-2 pregnant patients did not differ from those appeared in non-pregnant patients [155,161], however, in some cases severe complications effected pregnant women and fetuses causing premature births, fetal distress, Premature rupture of fetal membrane, Cesarean section [159], and maternal acute renal impairment, renal dysfunction, and renal failure [161][162][163]. It was also observed that upon SARS-CoV-2 infection, ACE2 receptor was downregulated thus lowering the level of Angiotensin 1-7 which can mimic or worsen preeclampsia [164].…”
Section: Pregnant Women and Neonatesmentioning
confidence: 86%
“…Clinical manifestations appeared in SARS-CoV-2 pregnant patients did not differ from those appeared in non-pregnant patients [155,161], however, in some cases severe complications effected pregnant women and fetuses causing premature births, fetal distress, Premature rupture of fetal membrane, Cesarean section [159], and maternal acute renal impairment, renal dysfunction, and renal failure [161][162][163]. It was also observed that upon SARS-CoV-2 infection, ACE2 receptor was downregulated thus lowering the level of Angiotensin 1-7 which can mimic or worsen preeclampsia [164].…”
Section: Pregnant Women and Neonatesmentioning
confidence: 86%
“…The circulating higher levels of mater- [24]. In fact, SARS-CoV-2 enters the cell via the angiotensin-converting enzyme 2 (ACE2) receptor, which is upregulated in normal pregnancy [25]. For the placenta-related pathology, we will focus our discussion on the temporal expression of ACE2 throughout gestation for possible propagation of SARS-CoV-2 in the placenta in infected women and ensuing consequences [26].…”
Section: Discussionmentioning
confidence: 99%
“…While, previous study, was not promoting the use typical D-dimer rise during gestation as indicator for unfavorable prognosis in pregnancy [66], recent study, justified a significant D-dimer elevation (cutoff; 3-4fold above ULN) as clear indication for hospital admission irrespective of absence of other suggestive symptoms [77]. Upon binding to ACE2, SARS-CoV-2 causes its downregulation, thus lowering angiotensin-(1-7) levels, which can mimic/worsen the vasoconstriction, inflammation, and pro-coagulopathic effects that occur in preeclampsia [25]. positive cases [79].…”
Section: Discussionmentioning
confidence: 99%
“…The normal physiological changes in the third trimester of pregnancy create pro-inflammatory state so that a woman's body prepares for the beginning of the parturition. SARS-CoV-2 infection is associated with increased cytokine production and this causes the immune system to change similarly to the third trimester, causing uterine contractions, amniotic fluid rupture, and birth [9,16]. The systematic review of Turan O, et al [17] showed that the rates of maternal mortality, stillbirth, and neonatal mortality were 1.6%, 1.4% and 1.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%